2006
DOI: 10.5433/1679-0359.2006v27n3p471
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do desempenho reprodutivo de um rebanho bovino de corte naturalmente infectado com o BoHV-1, BVDV e Leptospira hardjo

Abstract: ResumoO objetivo desse trabalho foi avaliar a performance reprodutiva de um rebanho bovino de corte, criado extensivamente, naturalmente infectado pelo herpesvírus bovino 1 (BoHV-1), pelo vírus da diarréia viral bovina (BVDV) e pela Leptospira hardjo. No rebanho, constituído por 1.331 fêmeas, foram selecionados aleatoriamente 208 animais que foram subdivididos em três grupos: i) 60 novilhas virgens; ii) 60 vacas de primeira cria; iii) 88 vacas com duas ou mais crias. No período correspondente a uma estação de … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 8 publications
0
3
1
4
Order By: Relevance
“…This occurrence was lower than the 98% (204/208) observed by Junqueira et al (2006) in female beef cattle (Nelore and Red Angus x Nelore) aged over 24 months from the west of São Paulo state and the 64% (2,261/3,533) related by Brito et al (2010) in female cattle older than 24 months from different regions of the Goiás state. This lower prevalence obtained in the present study can be attributed to the different cutoff points used in the VN technique, and by the fact that the authors of previous studies considered positive animals with Ab titration ≥8 and ≥4, respectively, while in the present study a cutoff point ≥10 was assumed.…”
Section: Resultscontrasting
confidence: 53%
“…This occurrence was lower than the 98% (204/208) observed by Junqueira et al (2006) in female beef cattle (Nelore and Red Angus x Nelore) aged over 24 months from the west of São Paulo state and the 64% (2,261/3,533) related by Brito et al (2010) in female cattle older than 24 months from different regions of the Goiás state. This lower prevalence obtained in the present study can be attributed to the different cutoff points used in the VN technique, and by the fact that the authors of previous studies considered positive animals with Ab titration ≥8 and ≥4, respectively, while in the present study a cutoff point ≥10 was assumed.…”
Section: Resultscontrasting
confidence: 53%
“…The percentages of observed titers (49.41%, 81.30% and 90% respectively) consistent with active infection. High rates of these infections in cattle herds in Brazil are described by other authors (Junqueira et al 2006, Aono et al 2013, Pereira et al 2013) ( Table 2). The studies of the three previously cited authors used the same cutoff point of this study for serological reactions, however herds or sample had different characteristics.…”
Section: Discussionmentioning
confidence: 65%
“…It is noteworthy that the cows were vaccinated twice a year against leptospirosis, and samples were collected from different properties. Junqueira et al (2006) evaluated a herd of beef cattle in São Paulo state, where the reproductive management consisted of artificial insemination and re-mating with bull and found the following prevalence rates: 81.8% for BoHV-1, 98.9% for BVDV and 79.5% for Leptospira sp. In a herd of unvaccinated Girolando cows (n=84), Pereira et al (2013) found seropositivity rates of 100%, 52.4%, and 45.2% for BoHV-1, BVDV and leptospirosis, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…O isolamento do vírus em cultivo de células de origem bovina é o melhor método de diagnóstico, podendo ser identificado pelas técnicas de imunofluorescência ou virusneutralização. A soroneutralização e o ensaio imunoenzimático (ELISA) são utilizados na rotina para detecção de anticorpos contra o BoHV-1 (BARBOSA et al, 2005;JUNQUEIRA et al, 2006;QUINCOZES, 2005;ROCHA et al, 2001). A vacinação para IBR/IPV é utilizada para o controle da enfermidade, embora não impeça a infecção pelo vírus, diminui consideravelmente a incidência e as manifestações clínicas (HALFEN;VIDOR, 2001).…”
Section: Introductionunclassified